1/f Noise responses of Ultra-Thin Body and Buried oxide FD-SOI PMOSFETs under total ionizing dose irradiation. Issue 11 (2nd December 2021) - Zhang, Ruiqin; Zheng, Qiwen; Lu, Wu; Cui, Jiangwei; Li, Yudong; Guo, Qi
Abstract : This paper investigates the low frequency noise degradation of commercial Ultra-Thin Body and Buried oxide Fully Depleted Silicon on Insulator (UTBB FD-SOI) PMOSFETs are under Total Ionizing Dose (TID) irradiation. According to the experimental results, the 1/ f noise of the conduction channel in studied transistors increases differently after irradiation. Based on the carrier number fluctuation (CNF) model with additional carrier mobility fluctuations (CMF), we expand the process of 1/ f noise changes at the front and back gates in UTBB FD-SOI devices during TID irradiation. Moreover, the relationship between channel Width/Length ratio ( W / L ) and the 1/ f noise normalized power spectral density at the front gate before and after TID irradiation is also discussed. The trend reducing W / L condition can alleviate 1/ f noise degradation in transistors is consistent with the expended theory, which can be a practical reference to develop the UTBB FD-SOI radiation-hardening technology.